2015
DOI: 10.1002/jpln.201500128
|View full text |Cite
|
Sign up to set email alerts
|

Water retention properties of a sandy soil with superabsorbent polymers as affected by aging and water quality

Abstract: Hydraulic properties, specifically the water holding capacity of soils, play a key role in the ability of soils to sustain plant growth. Additions of hydrophilic polymers (superabsorbents) can improve the water holding capacity of sandy soils. This has led to practical applications of these materials particularly in arid regions and countries, where water is the limiting factor for plant production. The objectives of this study are to investigate how effective hydraulic properties of polymer-soil mixtures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 31 publications
(37 reference statements)
5
46
0
3
Order By: Relevance
“…Our data (Fig. 3) further suggest that, based on the findings of Banedjschafie and Durner (2015), the higher water content in the soil-SAP mixtures compared with the soil alone combined with the linear decay of the drying curves for the soil-SAP mixtures, have a substantial contribution to plant available water over that provided by the soil alone.…”
Section: Mixtures Containing 05 1 and 2% Sapsupporting
confidence: 61%
See 2 more Smart Citations
“…Our data (Fig. 3) further suggest that, based on the findings of Banedjschafie and Durner (2015), the higher water content in the soil-SAP mixtures compared with the soil alone combined with the linear decay of the drying curves for the soil-SAP mixtures, have a substantial contribution to plant available water over that provided by the soil alone.…”
Section: Mixtures Containing 05 1 and 2% Sapsupporting
confidence: 61%
“…The application of SAP increased soil water content at field capacity and at permanent wilting point, which may lead to a considerable increase in available water content in soils of different texture used under various crops' management (Karimi et al, 2009;Agaba et al, 2010;Shahid et al, 2012;Banedjschafie and Durner, 2015;Montesano et al, 2015). This increase in the content of plant available water can, under conditions of climate change, mitigate abiotic stress (plant water shortage, high temperature and salinity stress); it could thus enable longer intervals between consecutive irrigations, and improve plant growth rate and performance (El-Hady et al, 1981;Baker, 1991;Silberbush et al, 1993;Singh, 1998;Hüttermann et al, 1999;Viero et al, 2002;Han et al, 2005;Beniwal et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of superior properties compared to traditional materials such as sponges, they are widely used in hygiene (Kosemund et al 2009), agriculture (Guo et al 2005;Liang et al 2009), drug delivery (Reddy et al 2011;Oun et al 2014), and water purification (Zheng et al 2010;Wang et al 2011). The research on the use of superabsorbents as water and fertilizer managing materials for the renewal desert environment (Banedjschafie and Durner 2015) and slow release fertilizers (Li et al2016;Yamamoto et al 2016) has attracted great attention, and encouraging results have been observed, as they can reduce irrigation water consumption, lower the death rate of plants, and increase plant growth rate (Parvathy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the capacity of the polymer to retain water decreased progressively by about one-quarter over a 100-day experiment, presumably as the polymer sorbed Pb . Banedjschafie and Durner (2015) also revealed that the water holding capacity of cross-linked polymers in sand deceased by about half during a period of six months, which they attributed to the accumulation of salts. In addition, soil enzymatic activities such as urease (which catalyses the hydrolysis of urea to CO 2 and NH 3 ) were inhibited by the application of polymer (de Varennes et al, 2010) suggesting potential toxicity.…”
Section: Soil Amendmentsmentioning
confidence: 98%